2014
DOI: 10.1124/dmd.113.054940
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics, Metabolism, and Clearance Mechanisms of Tofacitinib, a Janus Kinase Inhibitor, in Humans

Abstract: Tofacitinib is a novel, oral Janus kinase inhibitor. The objectives of this study were to summarize the pharmacokinetics and metabolism of tofacitinib in humans, including clearance mechanisms. Following administration of a single 50-mg 14 C-labeled tofacitinib dose to healthy male subjects, the mean (standard deviation) total percentage of administered radioactive dose recovered was 93.9% (63.6), with 80.1% (63.6) in the urine (28.8% parent), and 13.8% (61.9) in feces (0.9% parent). Tofacitinib was rapidly ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
210
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(223 citation statements)
references
References 20 publications
5
210
1
7
Order By: Relevance
“…The inhibitors have been commonly used in other studies (32, 33). We used tofacitinib doses that were within range observed in the plasma of subjects treated with this inhibitor(34, 35). Following JAK inhibition, S. typhimurium -infected intestinal myeloid cells secreted increased pro-inflammatory IL-1β and IL-8 levels in a JAK inhibitor dose-dependent manner; a similar increase was observed in peripheral MDMs (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitors have been commonly used in other studies (32, 33). We used tofacitinib doses that were within range observed in the plasma of subjects treated with this inhibitor(34, 35). Following JAK inhibition, S. typhimurium -infected intestinal myeloid cells secreted increased pro-inflammatory IL-1β and IL-8 levels in a JAK inhibitor dose-dependent manner; a similar increase was observed in peripheral MDMs (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has a short pharmacokinetic half-life of ϳ3 h and is rapidly absorbed (time to peak concentration is ϳ0.5 h) and eliminated (13). In a cellular setting, tofacitinib demonstrates preferential inhibition of signaling pathways associated with JAK1 and/or JAK3 (43).…”
Section: Jak Inhibition With Tofacitinibmentioning
confidence: 99%
“…The mean terminal plasma half-life of TOFA is 3.2 hours [37] and it has been previously shown that discontinuation of TOFA after short-term treatment in vitro allows normal reactivation of lymphocytes within four days [38]. Therefore, the effect at the time point of aerosol allergen challenge cannot be attributed to the transient action of TOFA, since the last application of TOFA was given 18 days before.…”
Section: Discussionmentioning
confidence: 99%